Illustration of Rapid Urban Growth in Surkhet Valley of Nepal via Land Use and Land Cover Dynamics - Budha, Padam Bahadur; Bhardwaj, Ashutosh; Thapa, Rajesh Bahadur (Geoplanning: Journal of Geomatics and Planning, 2023)
Surkhet Valley hosts Birendranagar City which is the capital of Karnali Province of Nepal and there is a rapid change in the landscape of this valley. This change can be attributed to its designation as an administrative capital and the leading economic center of the province. Thus, this study aimed to observe the changing land use and land cover (LULC) patterns of Surkhet Valley. Object-based image analysis was carried out for image classification for Landsat images of years 1989, 1999, 2009, and 2019. Key findings, for the area of 103.15 km2 Surkhet Valley, showed decreasing area of cultivated lands and increasing spatial coverage of built-up areas. The cultivated lands that measured 42 km2 for the year 1989 had plummeted to just 28.23 km2 in 2019. On the other side, the area covered by built-up class was only 1.16 km2 in 1989 which rose to 15.41 km2 in 2019. The changes in LULC coverage of other classes such as forests, shrub/grassland, sand, and water were negligible. The rate of change in the area of LULC classes built-up and cultivation was near but in the opposite direction. Built-up had an increasing rate of 0.49 km2year-1 while cultivation area had a decreasing rate of -0.46 km2year-1. When the built-up area of 2019 was compared to the base area of 1989 it had a gain of 1270.46% indicating its rapid growth in the past three decades. These reflected an increasing trend in spatial coverage of built-up areas indicating rapid urban growth.